KAJIAN TEOLOGIS TENTANG PAEDOCOMMUNION BERDASARKAN TEKS 1 KORINTUS 10:16-17 DAN IMPLIKASINYA BAGI GEREJA PRESBITERIAN di Indonesia - Oce Marlince Seo (STT-RAI Batam, 2024)
ABSTRACT The concept of the church that we know in the New Testament has its roots in the Old Testament. This concept is closely related to God's work in freeing the Israelites from slavery in Egypt. This act of liberation became the basis for the formation of God's people (qahal Yahweh), namely the Israelites to become God's people. Based on the understanding above, we can conclude that the Church in the New Testament is the New Israel. If the Church is the new Israel then the church can also be described as the Family of God (Familia Dei), then as the Family of God, the church is a fraternal community as children of one Father, redeemed by the blood of Christ and baptized in one baptism in the name of God the Father, The Son and the Holy Spirit, to partake at one Banquet Table of God's salvation and welcome the coming of the Kingdom of God in perfection. In the reality of ministry in the Protestant Church today, especially in the Presbyterian Church in Indonesia, children who are part of the Familia Dei are rejected from the Communion Table. In fact, the service of the Sacrament of Holy Communion to children (Paedocommunion) is also a continuation of what is written in the Old Testament regarding the Easter Meal, that if children are involved in the Easter Supper, then in today's Holy Communion children should be included too. The Sacrament of Holy Baptism is the basis for receiving the Sacrament of Holy Communion and children who have received the service of the Sacrament of Holy Baptism (Paedobaptism) are eligible to receive the Sacrament of Holy Communion (Paedocommunion), because the meaning of Holy Communion is the Covenant, the sign and seal of Christ, it is also food and spiritual drink for the soul. ABSTRAKS Konsep gereja yang kita kenal dalam Perjanjian Baru berakar dari Perjanjian Lama. Konsep tersebut berkaitan erat dengan karya Allah yang membebaskan bangsa Israel dari perbudakan di Mesir. Tindakan pembebasan inilah yang menjadi dasar untuk pembentukan umat Allah (qahal Yahweh) yakni bangsa Israel menjadi umat milik Allah. Berdasarkan pengertian di atas, maka dapat kita simpulkan bahwa Gereja dalam Perjanjian Baru adalah Israel Baru. Jika Gereja adalah Israel baru maka gereja juga dapat digambarkan sebagai Keluarga Allah (Familia Dei), maka sebagai Keluarga Allah, gereja merupakan persekutuan persaudaraan sebagai anak-anak dari satu Bapa, yang ditebus oleh darah Kristus dan dibaptis dalam satu baptisan dalam nama Allah Bapa, Anak dan Roh Kudus, untuk mengambil bagian dalam satu Meja Perjamuan keselamatan Tuhan dan menyongsong datangnya Kerajaan Allah dalam kesempurnaan. Dalam realita pelayanan di Gereja Protestan pada masa kini khususnya di Gereja Presbiterian di Indonesia, anak-anak yang adalah bagian dari Familia Dei ditolak dari Meja Perjamuan. Padahal pelayanan Sakramen Perjamuan Kudus pada anak (Paedocommunion) juga adalah kelanjutan dari apa yang tertulis dalam Kitab Perjanjin Lama tentang Perjamuan Paskah, bahwa jika dalam Perjamuan Paskah anak dilibatkan maka dalam Perjamuan Kudus sekarang ini seharusnya anak diikutsertakan juga. Sakramen Baptisan Kudus adalah dasar untuk menerima Sakramen Perjamuan Kudus dan anak yang sudah mendapat pelayanan Sakramen Baptisan Kudus (Paedobaptis) layak untuk diterima dalam Sakramen Perjamuan Kudus (Paedocommunion), karena makna dari perjamuan Kudus adalah Perjanjian, tanda dan materai dari Kristus, juga adalah makanan dan minuman rohani bagi jiwa.